Diversity, Equity, and Inclusion Among Anesthesiology Trainees - Shyam Patel; Keldon K. Lin; Adam J. Milam; Soojie Yu; Gwendolyn Raynor; Khurmi Narjeet; Ricardo Verdiner; Marlene E. Girardo; Lopa Misra (Mary Ann Liebert, 2022)
Background: Historically in medicine, women and minorities have been underrepresented. This trend is especially significant in the anesthesiology workforce. Objective: The goals of this study were to quantify the current state of diversity by race/ethnicity, gender, and sexual orientation among anesthesiology residents. Methods: An institutionally reviewed and validated survey was delivered through Qualtrics to 130 anesthesiology program directors. Topics addressed included gender identity, sexual orientation, racial and ethnic background, rationale for pursuing anesthesiology, and medical training experiences. The study was administered from February to April 2021; 135 anesthesiology residents responded to the survey. Results: The sample was 44.4% white (n?=?60), 54.1% male (n?=?73), and 83.7% (n?=?113) of respondents self-reported as straight or heterosexual. Respondents indicated that role models/mentors were somewhat or very important in their desire to pursue anesthesiology (n?=?85; 67.2%), 42% reported that having women/diverse faculty was somewhat or very important in their decision to pursue anesthesiology. Discrimination during the anesthesiology residency application process or as a resident ranged from 4.4% due to sexual orientation to 18.7% due to gender/gender identity and race/ethnicity. Conclusions: Experiences of discrimination based on race/ethnicity, gender, and gender identity continues to be a concern among anesthesiology trainees. Creating an environment that is inclusive and supportive of all trainees regardless of race/ethnicity, gender/gender identity, and sexual orientation is needed. Interventions and strategies to create an inclusive environment may improve diversity within anesthesiology.